2015
DOI: 10.1002/jsfa.7488
|View full text |Cite
|
Sign up to set email alerts
|

Application of visible/near‐infrared reflectance spectroscopy for predicting internal and external quality in pepper

Abstract: The present work has led to the development of multi-type calibrations for pepper quality parameters in intact and freeze-dried peppers. The majority of NIRS equations obtained were suitable for screening purposes in pepper breeding programs. Components such as pigments (xanthophyll, carotenes and chlorophyll), glucides, lipids, cellulose and water were used by modified partial least-squares regression for modeling the predicting equations. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 42 publications
(52 reference statements)
5
20
4
1
Order By: Relevance
“…Finally, it should be noted that the predictive capacity of the models obtained for TA by means of static and dynamic analysis allows to distinguish between low and high values for this parameter . Toledo‐Martín et al . obtained models for TA in 14 types of pepper with a predictive capacity (RPD cv = 1.4) similar to ours.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Finally, it should be noted that the predictive capacity of the models obtained for TA by means of static and dynamic analysis allows to distinguish between low and high values for this parameter . Toledo‐Martín et al . obtained models for TA in 14 types of pepper with a predictive capacity (RPD cv = 1.4) similar to ours.…”
Section: Resultssupporting
confidence: 84%
“…Finally, it should be noted that the predictive capacity of the models obtained for TA by means of static and dynamic analysis allows to distinguish between low and high values for this parameter. 15,19 Toledo-Martín et al 35 obtained models for TA in 14 types of pepper with a predictive capacity (RPD cv = 1.4) similar to ours. Flores et al 36 showed that the measurement of acidity-related parameters in intact fruits is notoriously difficult; nonetheless, the models developed for this parameter suggested that NIRS technology may be used for screening purposes.…”
Section: Prediction Of Color and Quality Parameters Using Mpls Regressupporting
confidence: 78%
See 2 more Smart Citations
“…In fact, there are very few articles that incorporate the use of this technology to measure quality parameters in pepper. Thus, Sánchez et al 9 assessed the viability of NIR spectroscopy to measure pesticide residues in intact, crused and dry extract system for infrared analysis (DESIR) peppers, whereas other authors or researchers [10][11][12][13] carried out the analysis of a number of quality parameters in different types of peppers.…”
Section: Introductionmentioning
confidence: 99%